PENGUATAN LITERASI SAMPAH MELALUI KOMUNIKASI PEMBANGUNAN UNTUK MEWUJUDKAN GAMPONG PRO IKLIM BEBAS SAMPAH - Thamara Putriani Br Matanari; Nabila Yaltavera (LPPM STAI Muhammadiyah Probolinggo, 2025)
Waste management has become a complex national issue in Indonesia, particularly in urban areas such as Banda Aceh. The high volume of waste not only causes environmental problems but also triggers social conflicts within communities. This community engagement program aims to raise awareness and encourage citizen participation in waste management through development communication and environmental literacy approaches. The method used was descriptive qualitative, with data collected through interviews, observations, and focus group discussions (FGDs).The results show that the informal development communication approach, based on interpersonal interactions, has effectively increased active community involvement in managing waste at the household level. Waste literacy has improved, as reflected in behavioral changes such as waste sorting, compost production, and participation in the management of the 3R Waste Processing Site (TPS 3R). In addition to creating a cleaner environment, the program has also generated economic benefits through the reuse of waste into valuable products. The application of Capra’s ecoliteracy principles is evident in the participatory, holistic, and sustainable waste management practices. Due to its success, Gampong Lambung has received several awards, including the Proklim Madya (2019) and Proklim Utama (2020).